Efektivitas Ekstrak Beberapa Tanaman Herbal terhadap Infeksi Ektoparasit pada Ikan Nila (Oreochromis niloticus) The effectiveness of Herbal Plant Extract to Infection of Ectoparasites on Tilapia (Oreochromis niloticus) - Desita Sari Br Ginting; Yunasfi Djayus; Nurmatias Nurmatias (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2014)
The main problem of Aquaculture is the diseases on the fish. Besides environmentally unfriendly, the using of chemicals as drugs against the diseasesalso producesthe new strain of the disease . The purpose ofthis study were to determine the effectiveness of using the extracts of garlic (Allium sativum), betel leafs (Piper betle), and papaya leafs (Carica papaya) against ectoparasites that infected thetilapia (Oreochromis niloticus) and to determine the immunity of some ectoparasites against each treatment. The methods used was experimental and observation by directly observing the occurrence or incidence of ectoparasites. Water quality parameters measured include temperature and degree of acidity ( pH ). The study was done for 45 days. Analisa Sidik Ragam used to determine the effect of each extract against ectoparasites on tilapia ( Oreochromis niloticus).The studyshowed that the papaya leaf (Carica papaya) has the best effectiveness in reducing the attack of ectoparasites on tilapia (Oreochromis niloticus) compared to garlic (Allium sativum) and betel leaf (Piper betle). The study also showed 12 kinds of ectoparasites that attacked the tilapia (Oreochromis niloticus). The highest incidence values found in the control, and then feed that mixed with garlic, then mixed with betel leafs and the lowest was the feed that mixed with papaya leafs.Keywords: Garlic, Betel Leafs, Papaya Leafs, Tilapia